Non-enzymatic electrochemical determination of bilirubin via sulfur-doped graphene and bimetallic nickel cobaltite conductive ink prepared paper-based screen-printed electrode - Dokur, Ebrar; Gorduk, Ozge; Sahin, Yucel (ELSEVIER SCIENCE SA, 2025)
Bilirubin (BR), a critical biomarker, serves as a vital indicator in the assessment of liver function and diagnose liver-related diseases. For these reasons, the determination and evaluation of BR levels is of great importance. This study presents the novel development of S-doped Graphene (S-Gr) and bimetallic Nickel Cobaltite (NiCo2O4) conductive ink for the determination of BR. This innovative approach enables the direct, single-step measurement of BR using flexible screen-printed electrode (SPE) fabricated with the S-Gr/NiCo2O4 conductive ink. Optimization processes were carried out to determine the most suitable conditions for the developed conductive ink. The developed S-Gr/NiCo2O4/G/SPE demonstrated no interference effects on the oxidation of BR in the presence of any interfering species, with the reaction occurring in a single step. These results show that the observed response is specific to BR, thereby demonstrating that non-enzymatic oxidation of BR can be effectively accomplished by flexible electrochemical sensors designed with conductive ink specifically developed for BR determination. Furthermore, the developed flexible BR sensor has outstanding features, including a low detection limit of 0.703 mu M, a low quantification limit of 2.34 mu M, wide linear range, high sensitivity, and good stability. The SPEs were characterized using a range of techniques, including cyclic voltammetry, electrochemical impedance spectroscopy, energy-dispersive X-ray spectroscopy, field emission scanning electron microscopy, Xray photoelectron spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. The proposed flexible electrodes have the potential to contribute to the development of innovative devices for electrochemical sensors and wearable technologies.
Keywords: Conductive ink; Flexible electrode; Bilirubin; Nickel cobaltite; Sulfur-doped graphene; FLEXIBLE ELECTRODES; SENSOR; BINDER; NANOPARTICLES; POLYSTYRENE; SURFACTANT; INSIGHTS; Materials Science; Physics